Diferentes técnicas de diagnóstico empregadas na estimativa de prevalência populacional de infecção por Cryptosporidium felis em gatos domiciliados no município de Araçatuba, São Paulo - Silveira Neto, Luiz da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this work was to compare the diagnostic methods by capture enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (nested-PCR) to morphological analysis using the technique of flotation in water-ether followed by modified Kinyoun staining (microscopy) to estimate the shedding rate of Cryptosporidium spp. in stool samples of cats domiciled in urban area of municipality of Araçatuba, São Paulo State. Zoonotic potential of coccidian isolated in feces was investigated by molecular characterization. A total of 138 stool samples were collected random and proportionally from to cat population in each of the seven census areas belonging to the urban area. There was no disagreement between capture ELISA and microscopy (p = 1.0000) or between nested-PCR and microscopy (p = 0.1094); however, the degree of agreement varied from substantial (Kappa = 0.7948) to moderate (Kappa = 0.4647), respectively, in these diagnostic methods. Specificity of nested-PCR and ELISA capture were similar; however, the nested-PCR showed lower sensitivity, justified by the association between the intensity of the optical density and amplification of 18S rRNA subunit. We detected Cryptosporidium spp. in 9.4% of the samples by at least two diagnostic methods. With the 95% confidence, we estimate that shedding rate of Cryptosporidium oocysts ranged from 4.5% to 14.3% in the feline population of Araçatuba. All isolates sequenced showed 100% similarity with Cryptosporidium felis. We conclude that cats domiciled can contribute to environmental contamination of a municipality, although C. felis is not the primary etiologic agent of cryptosporidiosis in humans

Os objetivos deste trabalho foram comparar os métodos de diagnóstico por ensaio imunoenzimático (ELISA) de captura e reação em cadeia da polimerase (nested-PCR) à análise morfológica utilizando a técnica de centrífugo-flutuação em água-éter seguida de coloração de Kinyoun modificada (microscopia) para estimar a taxa de eliminação de oocistos de Cryptosporidium spp. na população de gatos domiciliados na zona urbana do Município de Araçatuba, São Paulo. O potencial zoonótico do coccídio isolado em fezes deste hospedeiro foi investigado por meio de caracterização molecular. Um total de 138 amostras fecais foi colhido de forma aleatória simples e proporcional à população de gatos de cada uma das sete áreas censitárias pertencentes à zona urbana do município. Não houve discordância entre ELISA de captura e microscopia (p = 1,0000) nem entre nested-PCR e microscopia (p = 0,1094); entretanto, o grau de concordância variou de substancial (Kappa = 0,7948) a moderado (Kappa = 0,4647), respectivamente, entre estes métodos. Especificidade da nested-PCR e do ELISA de captura foi semelhante; entretanto, a nested-PCR apresentou menor sensibilidade, justificada pela associação entre a intensidade da densidade óptica e a amplificação da subunidade 18S do rRNA. Detectamos oocistos de Cryptosporidium spp. em 9,4% das amostras por pelo menos dois métodos diagnósticos. Com intervalo de 95% de confiança, estimamos que a taxa de eliminação de oocistos desse protozoário na população felina do município variou de 4,5% a 14,3%. Todos os isolados sequenciados apresentaram 100% de similaridade com Cryptosporidium felis. Concluímos que gatos domiciliados possam contribuir para a contaminação ambiental de um município, ainda que C. felis não seja o principal agente etiológico da criptosporidiose em seres humanos
Keywords: Gato; Gato - Doenças; Criptosporidiose; Ensaio de imunoadsorção enzimática; Epidemiologia veterinaria; Enzyme-linked immunosorbent assay